Prevalence of hypothalamo pituitary dysfunction in patients of traumatic brain injury - K. V. S. Hari Kumar; M N Swamy; M A Khan (Indian Journal of Endocrinology and Metabolism, 2016)
Background: Traumatic brain injury (TBI) is common in young soldiers of armed forces leading to significant morbidity and mortality. We studied the prevalence of hypopituitarism following TBI and its association with trauma severity. Materials and Methods: We conducted a 12-month prospective study of 56 TBI patients for the presence of hormonal dysfunction. Hormonal parameters were estimated during the early phase (0–10 days posttraumatically) and after 6 and 12 months. Dynamic testing was done when required, and the results were analyzed by appropriate statistical methods. Results: Hormonal dysfunction was seen in 39 of the 56 (70%) patients at initial assessment. Persisting pituitary deficiencies are seen in 7 and 8 patients at the end of 6 months and 12 months, respectively. Hypogonadotropic hypogonadism, hypothyroidism, and growth hormone deficiency are the most common diagnoses. Initial severe TBI and plurihormonal involvement predicted the long-term hypopituitarism. Conclusion: Early hypopituitarism was common in severe TBI, but recovers in majority. Evaluation for the occult pituitary dysfunction is required during the rehabilitation of TBI patients.